Metachronous double primary cancer of epithelial and mesenchymal origins: A case report of a rare clinical phenomenon. Issue 49 (December 2017) - Wu, Hongzeng; Li, Ze; Feng, Helin; Zhang, Jinming
Abstract: Rationale: Metachronous double primary cancers from the same origin have previously been reported in several studies; however, the occurrence of double primary cancers from different tissue origins has not been reported earlier. Patient concerns: We analyzed 10 patients with requirement surgical treatment. Diagnoses: After over 6 months of the surgery, histopathological examination confirmed the presence of at least two neoplastic lesions with distinct histopathology at different locations. Interventions: These patients underwent surgery and the hematoxylin and eosin staining was performed according to standard protocol in all cases. Outcomes: Since the occurrence of multiple primary cancers is an extremely rare event, it is difficult to find a large sample size of patients with double primary cancers at one study center. All patients included in this study received surgical therapy twice and had a final tissue histopathologic diagnosis. Lessons: Based on our findings, it is concluded that a prolonged follow-up examination for cancer patients should be taken into consideration to provide early detection of secondary tumors and improve overall life expectancy of these patients. Furthermore, clinicians should be well aware of the possibility of cancer patients developing a second primary cancer of a different tissue origin.